Konflik dan Kontestasi Penataan Ruang Kota Surabaya - Aminah, Siti (Masyarakat: Jurnal Sosiologi, 2015)
This article summarizes two hypotheses. Firstly, the practices problem of spatial planning in urban areas, especially in Surabaya City, has led to the contestation and conflict among governmental actors, the public, and the power of capitalist/investor. Secondly, the use of spatial planning framework, in this case is the use of Local Regulation on Urban Planning and Land Use Number 3 year of 2007, has shown the partiality and strengthening investor by the government. These hypotheses are analyzed by using socio spatial approach. The research method used in this article is qualitative method and descriptive analysis. Related to the problems of spatial planning practices in Surabaya is actually a transformation indication in urban planning process. Space is not only produced and reproduced to the interest of capitalist class, but also restructured by changing the function of the space reserved for the public. This is relevant to the development cutting-edge spatial planning studies indicate that the practice of urban planning in urban area is a reflection of social, economy, and political conditions. Space is produced in the capitalist mode of production. The expression of urban space is a dialectic relationship between production, consumption, and administration (planning and implementation of policies).